ENKAPSULAN DARI MODIFIKASI TEPUNG LABU KUNING (Cucurbita moschata) DAN APLIKASINYA UNTUK MIKROENKAPSULASI ASAP CAIR - , FERRI ARDIANSYAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pumpkin is a fruit that contains high carbohydrates by which potentially processed into flour and its starch can be modified by enzyme to increase solubility. Polymer chains of starch are broken down by Î±-amilase enzyme into simple sugar such as dextrin, d-glucose and maltose which can be used as wall material (encapsulate) and as filler to protect volatile phenol compounds of liquid smoke to preserved it from evaporation. The objective of this research was to evaluate the characteristic of enzymatic modified pumpkins flour as wall material and filler. The microcapsule of liquid smoke was made through spray drying technique with inlet temperature of 130oC and outlet 60oC and 5 ml/minute flow rate whereas the filler dried through cabinet dryer with temperature of 60oC. Each of microcapsules and filler was made with three different total soluble solid concentrations consist of 11%, 13%, and 15%. The observed parameters in this study are moisture content, solubility time, product recovery, total phenols, efficiency, distribution size particle and morphology. This research is using complete randomized design with three replications. The results showed the best treatment microcapsules of liquid smoke and filler in concentration total soluble solid of 15%. Each of microcapsules and filler has moisture content of 2,64% and 2,15%, solubility time 77,10% in 8 seconds and 27,53% in 5 minutes, product recovery of 13,88% and 23,93%, total phenols of 0,24% and 1,52%, efficiency of 13,29% and 14,16%. SEM observation of microcapsules has agglomerated morphology and heterogent size while the filler has a porous morphology, cracked and rough surface and heterogent size.